Identification of Hub Genes and Construction of a Transcriptional Regulatory Network Associated With Tumor Recurrence in Colorectal Cancer by Weighted Gene Co-expression Network Analysis - Liu, Shengwei; Zeng, Fanping; Fan, Guangwen; Dong, Qiyong (Frontiers in Genetics, 2021)
Tumor recurrence is one of the most important risk factors that can negatively affect the survival rate of colorectal cancer (CRC) patients. However, the key regulators dictating this process and the exact mechanisms are understudied. This study aimed to construct a gene co-expression network to predict the hub genes affecting CRC recurrence, and to inspect the regulatory network of hub genes and transcription factors (TFs). A total of 177 cases from GSE17536 dataset were analyzed via weighted gene co-expression network analysis (WGCNA) to explore the modules related to CRC recurrence. Functional annotation of the key module genes was assessed through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The protein and protein interaction (PPI) network was then built to screen hub genes. Samples from the Cancer Genome Atlas (TCGA) were further used to validate the hub genes. Construction of TFs-miRNAs–hub genes network was also conducted using StarBase and Cytoscape approaches. In result, the turquoise module showed the most significant relevance with CRC recurrence. After identification and validation, a total of five genes (TIMP1, SPARCL1, MYL9, TPM2 and CNN1) were selected as hub genes. A regulatory network of TFs-miRNAs-targets with 29 TFs, 58 miRNAs, and 5 hub genes was instituted, including model GATA6-MIR106A-CNN1, SP4-MIR424-TPM2, SP4-MIR326-MYL9, ETS1-MIR22-TIMP1 and ETS1-MIR22-SPARCL1. In conclusion, the identification of these hub genes and the prediction of the Regulatory relationship of TFs-miRNAs-hub genes may provide a novel insight for understanding of the underlying mechanism for CRC recurrence.